Expression of (ZO-1 & PLVAP) Antibody in the Sulcus Medianus Organum of Rat - Majid Ali, Hayder; J. Kadhim, Hayder; Husam Ahmed, Fadhil; Salah Hasan, Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
The circumventricular organs (CVOs) are peculiar structures that border the brain ventricles; they are highly vascularized and lined by specialized ependymal cells called tanycytes. There are seven CVOs that are generally characterized by a deficient blood-brain barrier and can be classified into two main groups (sensory and secretory CVOs). The sulcus medianus organum (SMO) is a previously described CVO located at the floor of the fourth ventricle at the rostral part of the median sulcus; little information is available about this region of the brain. This research performed an immunohistochemical study considering the capillaries and the ependymal lining of this region to explore observations suggesting this region as a CVO. Twenty adult male rats (Rattus Norvegius Albinus) Aged 3-6 months were used to study the immunohistochemistry of the SMO & the median eminence (ME), which was used as a control region since it is a well-known CVO lined by specialized ependymal cells (tanycytes) and richly vascularized with fenestrated capillaries. The immunohistochemical study involved the use of the ZO-1 antibody to detect the tight junctions and the PLVAP antibody to explore the presence of fenestrated capillaries. The immunohistochemical labeling findings showed a ZO-1 antibody reactivity that forms a continuous green line at the apical aspects of the ependymal lining of both SMO & ME. The PLVAP antibody labeling showed a negative reactivity at the region of the SMO in comparison to the ME, which showed a positive reactivity. Conclusively, the SMO region contains ependymal lining cells that could be regarded as tanycyte-like cells, and the blood vessels in this region showed features indicating the presence of a blood-brain barrier. However, the presence of fenestrated capillaries cannot be excluded totally, and the use of vascular permeability study or electron microscopy to explore the ultra-structural properties of the ependymal lining and the blood vessels at that region was recommended.